2012
DOI: 10.1088/0029-5515/52/12/123017
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of the pellet deposition profile and ∇B-induced drift displacement in non-axisymmetric configurations

Abstract: Drift displacement during density homogenization is modelled for hydrogen pellets injected into the Large Helical Device (LHD). The pellet ablation and deposition profiles are simulated for neutral-beam injection heated plasmas and are shown to reproduce well the main characteristics of the observed drift displacement for both low-field side and high-field side (HFS) injected pellets. The model describes the parallel expansion of ionized ablated pellet particle cloudlets (plasmoid) in non-axisymmetric magnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 36 publications
1
27
0
Order By: Relevance
“…7, [24]). Conversely, in stellarators, if the time τ EC is of the same order of magnitude as in tokamaks, the length Z c beyond which the IC becomes efficient is only half the toroidal period of the configuration, Z C ∼ πR m period , where m period is the number of periods [22], Fig. 6b.…”
Section: Physics Of Homogenizationmentioning
confidence: 99%
See 1 more Smart Citation
“…7, [24]). Conversely, in stellarators, if the time τ EC is of the same order of magnitude as in tokamaks, the length Z c beyond which the IC becomes efficient is only half the toroidal period of the configuration, Z C ∼ πR m period , where m period is the number of periods [22], Fig. 6b.…”
Section: Physics Of Homogenizationmentioning
confidence: 99%
“…Locally, the damping of the drift is very efficient and the material deposited at this place takes the shape of an overdense poloidal ring that expands in the toroidal direction more slowly than the matter deposited deeper in the discharge [25]. The model described above was implemented in different codes adapted to the tokamak configuration 2 or to the stellarators [22,28] and checked against experiments over a significant number of devices ([2, 3] and references therein, [22,[29][30][31][32]).…”
Section: Physics Of Homogenizationmentioning
confidence: 99%
“…However, close to the integer rational surfaces, it decreases down to 2πqR, where q is the safety factor, which explains the aforementioned major role of the iota profile in stopping the drift (Geulin & Pegourie 2022). The drift-damping produced by external currents is the dominant effect in tokamaks, whereas internal currents are dominant in helical configurations due to their shorter plasmoid-internal charge reconnection lengths (Matsuyama et al 2012a). However, a previous study in TJ-II revealed an interaction between outward-drifting plasmoids and low-order rational surfaces that can be attributed to the ECC effect (McCarthy et al 2021).…”
Section: Introductionmentioning
confidence: 98%
“…The resultant ∇B-drift arises from a modification of the potential distribution inside a plasmoid (Rozhansky et al 2004;Parks & Baylor 2005;Pégourié et al 2007). For arbitrary magnetic configurations, the main term of cloud drift acceleration is given by (Köchl et al 2012;Matsuyama et al 2012a)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation